Health Benefits of Three Wild Leafy Vegetable in “Lalapan” as Sundanese Traditional and Ethnic Foods - Kodir, Reza Abdul; Moektiwardoyo, Moelyono (Indonesian Journal of Biological Pharmacy, 2022)
Various ethnics of the world have a long history on using their surrounding as the source of foods. Foods which are act as product of traditional ethnic knowledge known as traditional and ethnic foods (TEF). Vegetables are one of the main ingredients of TEF. As sources of many combination of phytonutrients, vegetables offer various health benefits. As a country with long history of agricultural practice, Indonesia also has abundant knowledge of how Indonesian ethnics process and consume vegetables.Vegetables, in Sundanese tradition, usually consumed as “lalap” or “lalapan”. Some lalapan are cultivated vegetables and some others are come from wild sources. This article discuss the health benefits of wild source lalapan, which can be found in natural habitat.